Tunable thermal properties of the biphenylene and the lateral heterostructure formed with graphene: A molecular dynamics investigation - Cui, Qiang; Ren, Kai; Zheng, Ruxing; Zhang, Qiuhua; Yu, Luxin; Li, Jianping (Frontiers in Physics, 2022)
Recently, biphenylene was successfully synthesized as a novel allotrope of carbon. In this investigation, the non-equilibrium molecular dynamics calculations are conducted to explore the intrinsic thermal properties of the biphenylene. The isotropic thermal conductivity of the biphenylene is obtained, which is also sensitive to the size and the temperature. Furthermore, the graphene/biphenylene lateral heterostructure is constructed to possess an interfacial thermal conductance of about 2.84 × 109 W·K‒1·m‒2. The external tensile strain can induce a redshift of the vibrational density of states of the pristine graphene and biphenylene, and the improved overlap also results enhanced heat flux in the biphenylene/graphene heterostructure. Our approach can provide a theoretical guidance to design the thermal management device based on graphene and biphenylene.